Materials’ Characterization and Properties of Multiwalled Carbon Nanotubes from Industrial Waste as Electromagnetic Wave Absorber - Fadzidah Mohd Idris; Khamirul Amin Matori; Ismayadi Ismail; Idza Riati Ibrahim; Rodziah Nazlan; Farah Nabilah Shafiee; Mohd Shamsul Ezzad Shafie (Springer, 2024)
Indexed by WOS/Scopus/ERA